DAMPAK KEBIJAKAN PERTAMBANGAN TERHADAP KETAHANAN MASYARAKAT DESA (Studi Kasus Desa Sanggula Kecamatan Moramo Utara Kabupaten Konawe Selatan) - Halisra; Patta Hindi Asis; Yunitawati Lampasa; Riston G Ahmad (Journal Publicuho, 2024)
This study aims to determine the IMPACT OF MINING POLICY ON VILLAGE COMMUNITY RESILIENCE (Case Study of Sanggula Village, North Moramo District, South Konawe Regency). The method uses a qualitative approach and is analyzed thematically to identify patterns and themes that emerge related to the impact of mining on community resilience. The results of the study show that the economic impact of mining in Sanggula Village is not evenly distributed in the local community. Although the overall income of the community has increased, the distribution of benefits has not improved the welfare of the local community. Most of the benefits are only enjoyed by a handful of groups, while most people only experience negative impacts such as damage to agricultural land and sources of livelihood. Mining policies need to consider the survival of local communities in North Moramo so that their standard of living is better than before the mining business permit.